2019
DOI: 10.1080/20550324.2019.1669925
|View full text |Cite
|
Sign up to set email alerts
|

Synthesize of dendritic fibrous nano-silica functionalized by cysteine and its application as advanced adsorbent

Abstract: L-Cysteine-modified dendritic fibrous nanosilica grafted by amine groups (Cys-DFNS-NH 2 ) have been synthesized by a novel hydrothermal method. The N2 adsorption-desorption isotherms analysis on the Cys-DFNS-NH 2 show that the average pore volume and surface area of the prepared fibrous Cys-DFNS-NH 2 were 2.2 cm 3 /g and 205 m 2 /g, respectively, while the average pore size is 6.06 nm. Adsorption behavior of the Cys-DFNS-NH 2 for Cd 2þ , Cu 2þ , Ag þ , and Pb 2þ was investigated by electrochemical methods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Then 50 μL 3-aminopropyltriethoxysilane (APTES) was added to the mixture and refluxed for 20 h at 80 °C. Then the mixture was separated and washed with toluene several times and dried at 80 °C for at least 24 h 63 .…”
Section: Methodsmentioning
confidence: 99%
“…Then 50 μL 3-aminopropyltriethoxysilane (APTES) was added to the mixture and refluxed for 20 h at 80 °C. Then the mixture was separated and washed with toluene several times and dried at 80 °C for at least 24 h 63 .…”
Section: Methodsmentioning
confidence: 99%
“…Also, after surface functionalization, there was no noticeable change in the fibrous and spherical structure of the KCC-1, and the structure remains intact. It is reported that the existence of nanoporous silica fibers in the structure of KCC-1 efficiently renders molecular accessibility to the surface of KCC-1 in comparison to other types of mesoporous silica materials which makes KCC-1 as an attractive candidate for drug delivery and controlled release applications 49 , 87 , 88 .
Figure 2 TEM images of ( a ) KCC-1 and ( b ) KCC-1-NH 2 particles.
…”
Section: Resultsmentioning
confidence: 99%
“…The large surface area of the DFNS promotes more active sites for grafting functional groups with excellent chemical, mechanical, and thermal stability [30] . These features have made it an ideal candidate as a support material for many organic amine moieties, [31] organometallic complexes, [32] organic molecules, [33] metals, [34] metal oxides, [35] peptides, [36] polymers, [37] proteins, [38] enzymes, [39] etc. Therefore, DFNS ‐based materials have broad applications in drug delivery, gas capture, energy storage, biosensing, molecular probes, affinity ligands, and various adsorbents [36,40] .…”
Section: Introductionmentioning
confidence: 99%